Indirect Spectrophotometric Determination of Mebendazole Using Methyl Orange Dyein the Presence of the Oxidizing Agent NBS - Rasha Z. Abdulhadi, Dawood Habboo Mohammed, (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To develop a swift , simple, accurate and sensitive spectrophotometric method for determination of mebendazole (MBZL) in pure and pharmaceutical formulations. Methods: The suggested method depend on oxidation of MBZL with known excess amount of N-bromosuccinimide ( NBS ) in acidic medium and after reaction is insured to be complete , the surplus NBS is estimated by de colorization of methyl orange (MO) dye and measuring the absorbance of surplus dye at 508 nm. A linear calibration curve was obtained over the concentration range 2.5– 25 μg.ml-1 with correlation coefficient of 0.9997. The molar absorptivity and sandell's sensitivity index values were determined to be 1.505 × 104 L.mol-1.cm-1 and 0.019607 μg.cm-2. The limit of detection (LOD) and quantification (LOQ) were calculated to be 0.3736 and 2.553 μg.ml-1, respectively. The proposed method has been successfully applied to the determination of MBZL in available dosage form, the validity proposed method was confirmed by recovery study via standard addition technique .